Gambaran Variasi Gaya Mengajar Pendidik Di Taman Pendidikan Al-Qur’An - Deni Marlina (Jurnal Family Education, 2021)
This research was motivated by the phenomenon of the success of the TPA Raudhatul Islam Nagari Toboh Gadang Timur, Padang Pariaman Regency. This is evidenced by the large number of students and the many achievements obtained by Raudhatul Islam TPA students. Researchers suspect that the cause of the success of this TPA is due to the varied teaching styles of educators in learning activities. This study aims to describe the variations in teaching styles of educators at TPA Raudhatul Islam. This type of research is descriptive quantitative research. The population in this study were TPA Raudhatul Islam students totaling 180 people. The sampling technique used is purposive random sampling. Samples were taken with a specific purpose or purpose as many as 45 people. The data collection technique used is a questionnaire. Meanwhile, the data collection tool uses a list of statements (questionnaires). For the data analysis technique using the percentage formula. The results showed that the variation in the teaching style of educators was seen from the aspect of voice variation, focusing the attention of students, changing the position of educators and making eye contact with students when learning activities were categorized as good. This is evidenced by the majority of students giving frequent statements. Based on the results of the study, it is suggested that variations in the teaching style of educators in TPA should be maintained and if it can be improved